Study of the Environmental Kuznets Curve in the EU27 Countries Taking into Account Socio-Economic Factors and GHG and PM Emissions - Alicja Kolasa-Więcek; Iveta Šteinberga; Agnieszka A. Pilarska; Dariusz Suszanowicz; Małgorzata Wzorek (Energies)
The study of the relationship between human economic activity and the state of the environment in recent decades is reflected, among others, in the study of the environmental Kuznets curve (EKC) hypothesis. Numerous attempts have been made to examine the existence of the EKC by correlating various measures of environmental devastation with GDP per capita indicators. In this study, the aim and research gap were to compare and confirm/exclude the obtained results with the studies previously conducted by the authors, which referred to the analysis of the EKC in relation to general GHG emissions. In this analysis, GHG emissions per capita were assumed. In recent years, in the EU countries, more and more attention has been paid to research on the EKC focused on GHG emissions, and a certain research gap has been noticed in the direction of EKC analyses for PM2.5 and PM10. In the context of PM emissions, the very negative impact on human health should be emphasized. The authors decided to analyze the EKC hypothesis based on the current available data also in relation to PM emissions. In this study, a group of socio-economic variables in the form of GDP, gross electricity production, passenger cars, and population were used in relation to GHG, PM2.5, and PM10 emissions in the EU-27 countries. The study used multiple regression analysis to test the direction of the relationship between pollutant emissions and GDP. In the case of Germany, a negative correlation was obtained for GHG, PM2.5, PM10 emissions, and GDP. The EKC approach can be successfully used both in system awareness (qualitative) and quantitative studies to prepare scenarios of changes in greenhouse gas and PM emissions and to create strategic planning, manage resources, promote innovation, and in climate policy.